Mid-Long-Term Outcomes of Surgical Treatment of Legg-Calvè-Perthes Disease: A Systematic Review - Alessia Caldaci; Gianluca Testa; Eleonora Dell'Agli; Marco Sapienza; Andrea Vescio; Ludovico Lucenti; Vito Pavone (MDPI AG, 2022)
Background: Legg-Calvè-Perthes disease (LCPD) is a common childhood disease that usually occurs in 4- to 12-year-old children. Surgical treatment consists of femoral, pelvic, or combined osteotomies. This comprehensive review aimed to investigate the mid- and long-term outcome of the surgical treatment. Methods: A systematic review of PubMed, Science Direct, and MEDLINE databases was performed by two independent authors, using the keywords "outcome", "surgical treatment", "pelvic osteotomy", "femoral osteotomy", and "Legg-Calvè-Perthes disease" to evaluate studies of any level of evidence that reported the surgical outcome of LCPD. The result of every stage was reviewed and approved by two senior investigators. Results: A total of 2153 articles were found. At the end of the screening, we selected 23 articles eligible for full-text reading according to the inclusion and exclusion criteria. Our analysis showed that the main prognostic factors for surgical outcome in patients with LCPD are the age at onset and the degree of initial disease severity. Conclusions: Surgical treatment in patients older than 6 years has excellent results in Herring B and B/C hips and poor results in Herring C hips, with a slight advantage for patients between 6 and 8 years old.